2001
DOI: 10.1097/00004872-200101000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in four African-origin populations: current ‘Rule of Halves', quality of blood pressure control and attributable risk of cardiovascular disease

Abstract: With mortality risk now higher from non-communicable than communicable diseases in sub-Saharan Africa and elsewhere, systematic measurement, detection and genuine control of hypertension once treated can go hand-in-hand with other adult health programmes in primary care. Cost implications are not great. The data from this collaborative study suggest that such efforts should be well rewarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 17 publications
5
72
1
1
Order By: Relevance
“…High prevalence of obesity in women surpassed the levels reported in other developing countries in Latin America (Martorell et al, 2000) and Africa (Martorell et al, 2000;Mokhtar et al, 2001). Of interest, in our international study (Mbanya et al, 1999;Cruickshank et al, 2001), 35% of Afro-Caribbean women in Britain were obese, as were 37% of women in Pomerleau et al's (1999) study. The alarming level of obesity among women is of public health significance and a challenge to scarce resources.…”
Section: Discussionmentioning
confidence: 65%
“…High prevalence of obesity in women surpassed the levels reported in other developing countries in Latin America (Martorell et al, 2000) and Africa (Martorell et al, 2000;Mokhtar et al, 2001). Of interest, in our international study (Mbanya et al, 1999;Cruickshank et al, 2001), 35% of Afro-Caribbean women in Britain were obese, as were 37% of women in Pomerleau et al's (1999) study. The alarming level of obesity among women is of public health significance and a challenge to scarce resources.…”
Section: Discussionmentioning
confidence: 65%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In four of these, mean BP levels were not adjusted for age, [12][13][14][15] and one study based on the health Survey for England (the availability of data from two Health Surveys for England made this study unnecessary) did not provide information on standard deviations nor 95% CI to enable quantitative analyses. 15 One study did not provide information on BP values.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…15 One study did not provide information on BP values. 16 As a result, they were excluded. Nine studies provided data on African descent populations, [18][19][20]22,24,[26][27][28][29] and 12 provided data on South Asian descent populations.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Two authors supplied unpublished data. 11,15 Study selection and data extraction Of 14 papers included in the final analysis, 11 were cross-sectional surveys, most in the community, but some in occupational settings. Lane et al's 16 study includes some of the research participants in the study of Cruickshank et al 5 Meade et al's 3 was a cohort study and Whitty et al 12 reported crosssectional data from a cohort design.…”
Section: Search Strategymentioning
confidence: 99%
“…Mean systolic and diastolic BPs of the total study sample in two studies were calculated as the results were based on age-specific groups. 5,15 …”
Section: Search Strategymentioning
confidence: 99%